2016
DOI: 10.1007/s00405-016-4371-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile phone WeChat services improve adherence to corticosteroid nasal spray treatment for chronic rhinosinusitis after functional endoscopic sinus surgery: a 3-month follow-up study

Abstract: The objective of the study is to investigate the impact of receiving daily WeChat services on one's cell phone on adherence to corticosteroid nasal spray treatment in chronic rhinosinusitis (CRS) patients after functional endoscopic sinus surgery (FESS). This study was a two-arm, randomized, follow-up investigation. Patients with chronic rhinosinusitis with/without nasal polyps following bilateral FESS were randomised to receive, or to not receive, daily WeChat service on their cell phone to take corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 26 publications
0
73
0
Order By: Relevance
“…In contrast, nonnative English speaking patients were less likely to be adherent than native English‐speaking patients . Another study investigated adherence to intranasal corticosteroids after endoscopic sinus surgery by randomizing patients to a group with daily text messages, which served to educate the patients on the importance of intranasal corticosteroids as well as to remind them to take the corticosteroids, and to a group that did not receive daily reminders . At 90 days postsurgery, participants in the group who received daily text messages reported a 93% adherence to daily intranasal corticosteroids relative to the group who did not receive daily text messages and who reported only a 76% daily adherence to intranasal corticosteroids .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nonnative English speaking patients were less likely to be adherent than native English‐speaking patients . Another study investigated adherence to intranasal corticosteroids after endoscopic sinus surgery by randomizing patients to a group with daily text messages, which served to educate the patients on the importance of intranasal corticosteroids as well as to remind them to take the corticosteroids, and to a group that did not receive daily reminders . At 90 days postsurgery, participants in the group who received daily text messages reported a 93% adherence to daily intranasal corticosteroids relative to the group who did not receive daily text messages and who reported only a 76% daily adherence to intranasal corticosteroids .…”
Section: Discussionmentioning
confidence: 99%
“…This application offers integrated voice, text, and imaging sharing among a large number of active users, with 549 million monthly active users in 2016 [6]. Relative to traditional medical services, WeChat offers several advantages, including timely ability to contact the patient, a more personalized approach, more convenient operation, and lower costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the intervention time points occurred during the intervals between dialysis to avoid patient fatigue and weakness. Hence, the WeChat group communication not only met the needs of patients and their families regarding knowledge (Feng et al, ) but also provided patients with easily accessible psychological support. Considering the shortages in nursing staff and time in China, multimedia education may be a great strategy to enhance education outcomes and these strategies can be adopted by nursing managers.…”
Section: Discussionmentioning
confidence: 99%
“…All information can be retained for reference at any time anywhere as long as there is an internet connection. Recent studies have indicated that interventions delivered via WeChat regarding health management resulted in an improvement in adherence in orthodontic patients (Li et al, ) and chronic rhinosinusitis patients (Feng et al, ). Hence, WeChat may be an appropriate tool for improving the self‐management of haemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%